A ROLE OF COMMUNALISM IN BHISHAM SAHNI’S TAMAS - Devi, Wankhem Meratombi (ShodhKosh: Journal of Visual and Performing Arts, 2022)
Bhisham Sahni has a prominent place in Hindi fiction. Bhisham Sahni effectively portrays the reality of social life in his literature. His literature is sympathetic and realistic. Whatever Bhisham saw and experienced in the society became the subject of his literature. He has said about his works- "My experiences in the field of literature have been as simple and straightforward as in life. I believe that there is no such thing as literature apart from oneself. I will be able to create stories as I am." Like in the novel Tamas, the fire of communalism spread among the common people due to the divide and rule policy of the British. It depicts the helplessness of the people suffering from tension and terror and the society burning in this fire. Those who were killed in communal riots were mostly poor and weaker sections of society. These were the ones who were hurt the most. People from the upper class usually lived in safe conditions and helped each other.